Livelihood Strategy Of The Community Around The Kie Matubu Protected Forest In Jaya Village, Tidore City Island - Husen, Sadam S.; Salim, Tamrin (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2021)
The people in Jaya Village are people who still depend on their livelihood from utilizing forest products in their area, but even so there is no data or research conducted on any livelihood assets and how the livelihood strategies are carried out by the community around the forest in Jaya Village, Tidore City in utilizing their forest products. researchers are interested in doing this research. This research was carried out from September to November 2021 at the Jaya Village, Tidore Islands City. The data analysis used in this research is descriptive qualitative analysis. The results showed that there are 5 assets or livelihood capital owned by the community around the forest in Jaya Village, Tidore Islands City which include, natural assets, physical assets, financial assets, human assets, and social assets. There are 100% of respondents have natural assets in the form of land/land, 95% of respondents have physical assets (houses and vehicles), 60% of respondents have financial assets (savings money), 100% of respondents have human assets (family members who help make a living), and 100% of respondents also have social assets (mutual assistance activities). The strategy used by the community is a multiple strategy covering aspects of agriculture, animal husbandry, and other aspects (PNS, private employees, and laborers.)